Brundibar - Kushner, Tony (Michael Di Capua Books/Hyperion Books for Children, 2003)
When Aninku and Pepicek travel to the village to earn money to buy milk for their sick mother, they are befriended by three intelligent talking animals who help them overcome their fears.